Cover Picture: Bio‐adhesive Nanoporous Module: Toward Autonomous Gating (Angew. Chem. Int. Ed. 16/2021). Issue 16 (1st March 2021) - Jo, Hyuna; Kitao, Takashi; Kimura, Ayumi; Itoh, Yoshimitsu; Aida, Takuzo; Okuro, Kou
Abstract : A bio‐adhesive covalent organic framework with calmodulin as a proteinous gate is reported by Takuzo Aida, Kou Okuro et al. in their Research Article on page 8932 . The gate functionality is used for calcium‐ion‐triggered guest release from the nanopores.